2016
DOI: 10.1016/j.neuroimage.2016.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Brain correlates of phonological recoding of visual symbols

Abstract: Learning to read involves setting up associations between meaningless visual inputs (V) and their phonological representations (P). Here, we recorded the brain signals (ERPs and fMRI) associated with phonological recoding (i.e., V-P conversion processes) in an artificial learning situation in which participants had to learn the associations between 24 unknown visual symbols (Japanese Katakana characters) and 24 arbitrary monosyllabic names. During the learning phase on Day 1, the strength of V-P associations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 107 publications
2
5
0
Order By: Relevance
“…In addition, our results extend the scope of the functional properties of the left IFG and FuG in spelling, (Bitan et al, 2005;Planton et al, 2013;Rapp & Lipka, 2011;Rapp et al, 2016). In reading, the left FuG is thought to represent orthographic information on a visual form (Vinckier et al, 2007), but this view remains controversial (Madec et al, 2016;Price & Delvin, 2003;Rapp & Lipka, 2011). In fact, several studies showed that the left FuG is involved in accessing or storing orthographic information during both reading and spelling (Purcell et al, 2011;Rapp & Lipka, 2011;Tsapkini & Rapp, 2010).…”
Section: Evidence For Continuous Flow Of Information Between the Orthsupporting
confidence: 61%
“…In addition, our results extend the scope of the functional properties of the left IFG and FuG in spelling, (Bitan et al, 2005;Planton et al, 2013;Rapp & Lipka, 2011;Rapp et al, 2016). In reading, the left FuG is thought to represent orthographic information on a visual form (Vinckier et al, 2007), but this view remains controversial (Madec et al, 2016;Price & Delvin, 2003;Rapp & Lipka, 2011). In fact, several studies showed that the left FuG is involved in accessing or storing orthographic information during both reading and spelling (Purcell et al, 2011;Rapp & Lipka, 2011;Tsapkini & Rapp, 2010).…”
Section: Evidence For Continuous Flow Of Information Between the Orthsupporting
confidence: 61%
“…Other research has also indicated that the right parietal region plays a role in the perception of stimuli without any long-term representations arising simultaneously from the multiple sensory modalities (Kamke et al, 2012). The suppression effect in the right parietal and occipital regions at early time window indicates that the unfamiliar audiovisual information processing might rely more on the processing of the visual features (Calvert et al, 2001; Madec et al, 2016). It could be explained by the fact that Finnish participants who are naive to Chinese focused much more attention on the analysis of the spatial information of various strokes comprising the logographic character in order to be able to integrate the audiovisual stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to Raij et al (2000) and van Attelveldt et al (2004), we found no reliable heteromodal activation of the superior temporal gyrus/superior temporal sulcus when unimodal visual letters and speech sounds were presented. In addition, although in some cases (most likely when the task demands access to the letter name), the level of activation of the fusiform gyrus is modulated by inputs from upstream regions coding for phonological processing (Dietz et al, 2005;Xue et al, 2006;Madec et al, 2016), our results confirm that speech itself is not sufficient to lead to significant activation of the fusiform gyrus at the level of the visual word form area.…”
Section: Cross-modal Sensory Activationsmentioning
confidence: 47%
“…From that view, the fact that premotor activity was found to be equal in the speaking and writing tasks, and to also be equal but lower in the listening and reading tasks (see Figure 4), might suggest similar articulatory planning processing in the two first motor tasks, together with reduced motor reactivation in the two perceptual tasks. Note that, if this interpretation is correct, the degree of association between the letters and sounds specific to a given language might affect the results (see Madec et al, 2016). French is a non-transparent language where a letter can correspond to several sounds.…”
Section: Shared Neural Substrates In the Left And Medial Frontal Cortexmentioning
confidence: 99%
See 1 more Smart Citation